Psychometric properties of a Subjective Well-Being Scale for adolescent students from Bulgaria, Georgia, Hong Kong, Ireland, Mexico, Panama, Serbia, Spain, and the United Arab Emirates - Quiñonez Tapia, Francisco (2023)
The psychometric properties of a Subjective Well-being Scale were analyzed for adolescent students participating in the evaluations of PISA 2018. The sample included 67,503 adolescent students from Bulgaria, Georgia, Hong Kong, Ireland, Mexico, Panama, Serbia, Spain and the United Arab Emirates. Different models were evaluated for the Subjective Well-being Scale. Reliability was validated with the McDonald’s Omega coefficient, validity with the Confirmatory Factor Analysis and invariance with the Multigroup Factor Analysis. The Bifactorial model, with a general factor called Subjective Well-being and three specific factors called Satisfaction with Life, Positive Affects and Negative Affects, yielded the best fit indices. The analyses of the Subjective Well-being Scale applied to adolescent students from the four countries studied, yielded evidence of validity, reliability and invariance for different groups of adolescent students.